What's in it for me? all about food labelling [videorecording] - De Robbio, Michael (VEA, 2008)
Deals with the food labelling laws of Australia and New Zealand. Explains the role of Food Standards Australia New Zealand (FSANZ) and demystifies nutritional information found on labels, such as NIP, DI and GI. The importance of safe food storage and current guidelines relating to unpackaged foods are also discussed.